EXCHANGE RATE FLEXIBILITY, CAPITAL MOBILITY AND INFLATION TRANSMISSION IN MALAYSIA - Mansor H. Ibrahim (Journal of Management and Business, 2009)
The paper assesses the international transmission of inflation for a small economy, Malaysia, over three sample periods marked by different degrees of exchange rate flexibility. Contradicting to conventional wisdom of less pronounced foreign nominal influences under the flexible exchange rate regime, this research finds evidence that the inflation transmission from the US to Malaysia is strongest during the period marked by increasing exchange rate flexibility (i.e. 1993-1998). This research also observes significant inflation effects of exchange rate depreciation during the same period. While this research observe less pronounced impacts of the US during the limited exchange rate flexibility period (i.e. 1988-1999), the US influences are virtually absent during the recent fixed regime (i.e. 1998-2005). This research believes that the intensity of capital flows across the three periods might have explained the results.